DAYAH ON THE MOVE: SOCIAL ENGINEERING THROUGH ISLAMIC EDUCATION REFORMATION IN POST-CONFLICT ACEH, INDONESIA - Basri Basri; Andhika Jaya Putra; Teuku Zulfikar; Wahidah Wahidah (Islam Futura, 2023)
This article examines the institutional transformation of dayah in Post-Conflict Aceh referring to the leaders of four Islamic boarding schools’ (dayah) view points: the principal of Dayah Malikussaleh Aceh Utara, Dayah MUDI Mesra, Samalanga Bireun, Dayah Darul Munawwarah, Pidie Jaya and Dayah Darussalam Labuhan Haji, South Aceh; personnels in the Department of Dayah Education Affairs and members of the DPRA (members of Aceh House of Representative), our study found that the institutional transformation of the dayah began with changes in the government’s policies through the emergence of various regulations such as the Aceh Qanun (Aceh’ made law) and the Province of Aceh Governor's regulations. Furthermore, the transformation of funding sources, curriculum, facilities and infrastructure, human resource development, quality assurance and development of dayah, and cooperation and development of the dayah financial resource. This study concludes that the institutional transformation of the dayah has had an impact on increasing the functionality of the dayah in the midst of the times, changes in educational politics in Aceh and increasingly showing the modernization of the dayah while still maintaining a religious atmosphere in the Dayah environment.